Comparison of the efficacy between intensity-modulated radiotherapy and two-dimensional conventional radiotherapy in stage II nasopharyngeal carcinoma - Pan, Xin-Bin (Oncotarget, 2017)
We compared treatment outcomes in patients with stage II nasopharyngeal carcinoma (NPC) treated with intensity-modulated radiotherapy (IMRT) or two-dimensional conventional radiotherapy (2D-CRT). Stage II (2010 UICC/AJCC staging system) NPC patients treated with IMRT (n = 178) or 2D-CRT (n = 73) between January 2007 and December 2014 were retrospectively analyzed. Patients were matched using the propensity score-matching method. The primary endpoint was overall survival (OS). Secondary endpoints were local relapse-free survival (LRFS), regional relapse-free survival (RRFS), distant metastasis-free survival (DMFS), and disease-free survival (DFS). Acute and late toxicity reactions to IMRT and 2D-CRT were also compared. In an unmatched cohort of 251 patients, no significant survival differences were found between those receiving IMRT and those receiving 2D-CRT (5-year OS, 95.67% vs 94.44%, P = 0.0556; LRFS, 97.34% vs 98.59%, P = 0.6656; RRFS, 99.26% vs 100%, P = 0.6785; DMFS, 96.5% vs 98.63%, P = 0.7910; DFS, 92.2% vs 97.24%, P = 0.8719). In the propensity-matched cohort of 146 patients, 5-year OS (97.06% vs 94.44%, P = 0.1325), LRFS (96.75% vs 98.59%, P = 0.8869), RRFS (100% vs 100%, P = 1.0000), DMFS (98.63% vs 98.63%, P = 0.4225), and DFS (95.37% vs 97.24%, P = 0.5634) were similar between patients treated with IMRT or 2D-CRT. However, IMRT correlated with fewer acute and late toxicity reactions. Thus although IMRT provides no survival advantage, it has a lower incidence of toxicity than 2D-CRT in stage II NPC patients.